Gold - Alexander, Jed (Creston Books, 2022)
Who belongs and who doesn't? Do members of the same family all look the same? This wordless picture book plays with our assumptions about family. Is the little girl making food an uninvited guest, taking advantage of the bear family's open door? Or is she someone else entirely?